Identification of novel modulators of mitochondrial function by a genome-wide RNAi screen in Drosophila melanogaster - Chen, Jian; Shi, Xiaoying; Padmanabhan, Ranjani; Wang, Qiong; Wu, Zhidan; Stevenson, Susan C.; Hild, Marc; Garza, Dan; Li, Hao (Genome Research, 2008)
Mitochondrial dysfunction is associated with many human diseases. There has not been a systematic genetic approach for identifying regulators of basal mitochondrial biogenesis and function in higher eukaryotes. We performed a genome-wide RNA interference (RNAi) screen in Drosophila cells using mitochondrial Citrate synthase (CS) activity as the primary readout. We screened 13,071 dsRNAs and identified 152 genes that modulate CS activity. These modulators are involved in a wide range of biological processes and pathways including mitochondrial-related functions, transcriptional and translational regulation, and signaling pathways. Selected hits among the 152 genes were further analyzed for their effect on mitochondrial CS activity in transgenic flies or fly mutants. We confirmed a number of gene hits including HDAC6, Rpd3(HDAC1), CG3249, vimar, Src42A, klumpfuss, barren, and smt3 which exert effects on mitochondrial CS activities in vivo, demonstrating the value of Drosophila genome-wide RNAi screens for identifying genes and pathways that modulate mitochondrial function.